The longevity of famous people from Hammurabi to Einstein - De la Croix, David; Licandro, Omar (Springer Verlag, 2015)
We build a new sample of 300,000 famous people born between Hammurabi's epoch and Einstein's cohort, including their vital dates, occupations, and locations from the Index Bio-bibliographicus Notorum Hominum. We discuss and control for selection and composition biases. We show using this long-running consistent database that there was no trend in mortality during most of human history, confirming the existence of a Malthusian epoch; we date the beginning of the steady improvements in longevity to the cohort born in 1640-9, clearly preceding the Industrial Revolution, lending credence to the hypothesis that human capital may have played a significant role in the take-off to modern growth; we find that this timing of improvements in longevity concerns most countries in Europe and most skilled occupations.